The Explanation of the Abnormal Phenomena and Normal Investor’s Irrational Behavior in the Chinese A Stock Market from the - Fu, Qiang (2014)
Abstract I am very interested in the factors that affect investors’ decision-making process, and I think behavioral finance theory can be a good alternative to account for the anomalies of the Chinese stock market. In this dissertation, I will use behavioral finance theories to find out what factors and motives cause the anomalies in the growth enterprise module in the Chinese stock market and whether over-confidence effect have positive impact on the Chinese stock market trading volume. I will also execute questionnaire survey to observe whether irrational behaviors such as over-confidence, herd behavior, disposition effect and home biases are common problems among the Chinese investors, and try to account for the stories behind these irrational behaviors. In addition, I am also an individual investor and personally find that it is very difficult to be rational in the market. When I was trading I always have irrational trading behaviors, so I would like to observe how these behaviors affect people’s decision-making process when they construct their portfolios. This is also why I choose this dissertation topic. Based on my observations, I will also present recommendations for investors to help them outperform the Chinese stock market. I hope that my contribution from this article could give other investors who are interested in the Chinese stock market empirical reference.